2018
DOI: 10.1016/j.bbmt.2018.02.002
|View full text |Cite
|
Sign up to set email alerts
|

HLA-Matched Sibling versus Unrelated versus Haploidentical Related Donor Allogeneic Hematopoietic Stem Cell Transplantation for Patients Aged Over 60 Years with Acute Myeloid Leukemia: A Single-Center Donor Comparison

Abstract: Haploidentical related donor (HRD) allogeneic hematopoietic stem cell transplantation (allo-HSCT) was developed as a valid option for the treatment of acute myeloid leukemia (AML) in the absence of a matched donor. However, many investigators are reluctant to consider the use of this alternative in elderly patients, anticipating high morbidity. Here, we report a single-center comparison of HRD versus matched sibling donor (MSD) and unrelated donor (UD) allo-HSCT for patients with AML aged ≥60 years. Ninety-fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
40
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 28 publications
2
40
0
Order By: Relevance
“…In hematologic malignancies overall, allo-HCT is traditionally performed with use of HLA-identical sibling donors or unrelated donors, although it may be underutilized in highrisk MM. Because such donors are frequently unavailable, especially for non-Caucasian patients, allo-HCT from haploidentical related donors is being increasingly used, with decreased nonrelapse mortality (NRM) and favorable outcomes in disease control reported [7][8][9]. Data on the use of haploidentical transplantation in MM remain limited, although 2 small retrospective studies of haploidentical allo-HCT have reported encouraging results in patients with MM [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…In hematologic malignancies overall, allo-HCT is traditionally performed with use of HLA-identical sibling donors or unrelated donors, although it may be underutilized in highrisk MM. Because such donors are frequently unavailable, especially for non-Caucasian patients, allo-HCT from haploidentical related donors is being increasingly used, with decreased nonrelapse mortality (NRM) and favorable outcomes in disease control reported [7][8][9]. Data on the use of haploidentical transplantation in MM remain limited, although 2 small retrospective studies of haploidentical allo-HCT have reported encouraging results in patients with MM [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…The non‐significant trend for lower risk of chronic GVHD after haploidentical HCT as compared with matched HCT is in accordance with other reports (Blaise et al ., ; Devillier et al ., ; Robinson et al ., ; Santoro et al ., ). The possible explanation may be as follows.…”
Section: Discussionmentioning
confidence: 98%
“…These data suggest donor source and HLA-matching are not significantly correlated with transplant outcomes in these settings. Regardless, these publications have mainly described younger patients and lack data from older populations (Blaise et al, 2016;Devillier et al, 2018;Santoro et al, 2018).…”
mentioning
confidence: 99%
“…In large part due to the advent of new conditioning and GvHD prophylactic regimens, such complications have been significantly reduced. In multiple recent studies of transplants for hematologic malignancies, haploidentical transplants had noninferior and, at times, superior outcomes compared with MMUDs, UCB, and even matched donors [5,7,[10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27]. In this review, we will compare haploidentical donor outcomes with outcomes using other donor sources.…”
Section: Haploidentical Donormentioning
confidence: 99%
“…Importantly, these results were found to be similar in patients over 60 years of age undergoing Allo-HCT. Santoro et al and Devillier et al evaluated patients in this age group with AML who received transplants from either haploidentical donors or MUDs [5,24]. Neither study showed any difference in OS, LFS, or NRM [5,24].…”
Section: Haploidentical Vs Mrd and Mudmentioning
confidence: 99%